EFEKTIVITAS MODUL HUKUM DASAR KIMIA BERBASIS INKUIRI TERBIMBING TERINTEGRASI EKSPERIMENTERHADAP HASIL BELAJAR SISWA KELAS X MIA SMA PERTIWI 1 PADANG - Sausan, S (rc-institut, 2019)
This result aim to revealed the effectiveness basic law of chemistry based on guided inquiry integrated experiment module to learning outcomes for student class X MIA SMA Pertiwi 1 Padang. This type of research is quasi experiment, it by using Non-Equivalent control group design. This population research of student in class X MIA SMA 1 Pertiwi 2019/2020. The research sample was taken by purposive sampling technique. Class X MIA 3 as experiment class and X MIA 2 as control class has been choose. The research instrument cognitive (pretest-posttest) and psychomotor (the assessment sheet) assessement instruments.  Based on data analysis it is known that the cognitive value of the experiment class which is used basic law of  chemistry based on guided inquiry integrated experiment module obtain  the average value of the learning outcomes worth 88,07, control class without module is 78,7. Result of data analysis found that both of sample classes normally distributed and have homogenous variance. The result of the t test at the 0,05 level, the value of tscore is 2,17 > ttable 1,67. The result of  research  obtain that N-Gain experiment class is 0,7 (high) higher that control class 0,6 (medium). The psychomotor value of the experimental class is 83,3 and control class is 80,22.This show that class learning outcomes of the experiment class higher than the control class signitificantly conclution from the research prove that the basic law of  chemistry based on guided inquiry integrated experiment module is effective towards learning outcomes of class student X MIA SMA Pertiwi 1 Padang.